Major Role of the IL17/23 Axis in Psoriasis Supports the Development of New Targeted Therapies - Bugaut, Hélène; Aractingi, Sélim (Frontiers in Immunology, 2021)
Psoriasis is a frequent, chronic disease featured by cutaneous inflammatory plaques and/or arthritis. It may be associated with few other diseases, mainly Crohn’s disease and metabolic syndrome. The medical and psychosocial burden of psoriasis remains high even since biological treatments arose, stressing that the efforts to decipher its physiopathology are constantly needed. Tumor-necrosis factor α, interleukin (IL) 12 and IL17 have been previously associated with psoriasis and successfully targeted by monoclonal antibodies. IL17 in particular has been initially described as a T helper (Th) 17 - produced cytokine, but it is now established that other cell types, such as T lymphocytes, Mucosal-Associated Invariant T (MAIT) cells and Innate Lymphoïd Cells (ILC) 3 are also important sources of IL17 in the skin in response to inflammatory stimuli. Th17 phenotype has been shown to be stabilized by IL23, which is synthetized by macrophages and dendritic cells in response to Toll Like Receptors and C-type Lectin Receptors stimulation. Recent data also reported a crucial role for IL23 in MAIT17 and ILC3 homeostasis. Genome-wide association studies have found a significant link between IL23 receptor polymorphism and psoriasis susceptibility. IL23 signals through Janus kinase 2 and Tyrosine kinase 2, against which specific inhibitors are currently being tested. Monoclonal antibodies against IL17 and IL23 are only the beginning of a new avenue in psoriasis treatment. This review focuses on the molecular basis underlying IL23/IL17 axis blockade in psoriasis, and on future targets in this pathway.